Emergence of Bluetongue Virus Serotype 1 in French Corsica Island in September 2013. Issue 5 (24th January 2014) - Sailleau, C.; Viarouge, C.; Bréard, E.; Perrin, J. B.; Doceul, V.; Vitour, D.; Zientara, S.
Summary Since 2000, French Corsica Island has been exposed to the emergence of three different BT virus (BTV) serotypes: serotype 2 in 2000 and 2001, serotype 4 in 2003 and serotype 16 in 2004. Between 2005 and August 2013, no outbreaks have been reported in the French Island. At the beginning of September 2013, sheep located in the south of the island showed clinical signs suggestive of BTV infection. Laboratory analyses identified the virus as BTV serotype 1. Phylogenetic studies showed that the sequences of this strain are closely related to the BTV‐1 strain that was circulating in the Mediterranean basin and in Sardinia in 2012.